Cyclosporine A-related neurotoxicity after haploidentical hematopoietic stem cell transplantation in children with hematopathy - Yong Wang; Yongzhi Zheng; Jingjing Wen; Jinhua Ren; Xiaohong Yuan; Ting Yang; Jianda Hu (BMC, 2021)
Abstract Background To evaluate cyclosporine A (CSA)-related neurotoxicity after haploidentical hematopoietic stem cell transplantation (HID-HSCT) in children with hematopathy. Methods This retrospective case series study included children with hematopathy who underwent HID-HSCT at Fujian Medical University Union Hospital between February 2013 and January 2017. Results Fifty-one children (39 males) were included in the study with a median age of 8 (range, 1.1-18) years. Seven patients (13.7%) developed CSA-related neurotoxicity after a median 38 (range, − 3 to 161) days from HID-HSCT. Hypertension (5/7, 71%) was the most common prodrome. Brain magnetic resonance imaging showed posterior reversible encephalopathy syndrome in six patients and atypical abnormalities in one patient. One patient died from grade IV graft-versus-host disease (GvHD) on day + 160, and six patients were alive at the last follow-up. Four patients (71.4%) achieved complete remission, while two patients developed secondary epilepsy and exhibited persistent MRI and electroencephalogram abnormalities at the 5-year follow-up. Hypertension after CSA was more common in patients with CSA-related neurotoxicity than in those without (71% vs. 11%, P = 0.002). Five-year overall survival did not differ significantly between patients with CSA-related neurotoxicity (85.7 ± 13.2%) and those without (65.8 ± 7.2%). Conclusions The incidence of CSA-related neurotoxicity in children with hematopathy undergoing HID-HSCT is relatively high.